Structural insights into cGAMP degradation by Ecto-nucleotide pyrophosphatase phosphodiesterase 1 - Kato, Kazuki; Nishimasu, Hiroshi; Oikawa, Daisuke; Hirano, Seiichi; Hirano, Hisato; Kasuya, Go; Ishitani, Ryuichiro; Tokunaga, Fuminori; Nureki, Osamu (Nature communications, 2018)
ENPP1 (Ecto-nucleotide pyrophosphatase phosphodiesterase 1), a type II transmembrane glycoprotein, hydrolyzes ATP to produce AMP and diphosphate, thereby inhibiting bone mineralization. A recent study showed that ENPP1 also preferentially hydrolyzes 2′3′-cGAMP (cyclic GMP-AMP) but not its linkage isomer 3′3′-cGAMP, and negatively regulates the cGAS-STING pathway in the innate immune system. Here, we present the high-resolution crystal structures of ENPP1 in complex with 3′3′-cGAMP and the reaction intermediate pA(3′,5′)pG. The structures revealed that the adenine and guanine bases of the dinucleotides are recognized by nucleotide- and guanine-pockets, respectively. Furthermore, the structures indicate that 2′3′-cGAMP, but not 3′3′-cGAMP, binds to the active site in a conformation suitable for catalysis, thereby explaining the specific degradation of 2′3′-cGAMP by ENPP1. Our findings provide insights into how ENPP1 hydrolyzes both ATP and cGAMP to participate in the two distinct biological processes. Ecto-nucleotide pyrophosphatase phosphodiesterase 1 (ENPP1) is a type II transmembrane glycoprotein that hydrolyzes both ATP and cGAMP. Here the authors present the crystal structures of the extracellular domain of mouse ENPP1 in complex with 3′3′-cGAMP and the reaction intermediate pA(3′,5′)pG and discuss mechanistic implications.